Pilihan Hukum Dan Pilihan Forum Dalam Sengketa Konstruksi Yang Melibatkan Badan Usaha Jasa Konstruksi Asing - Saputri, Theodora Pritadianing (Widya Yuridika, 2025)
Project owners in Indonesia often involve foreign contractors in their construction projects. In projects that involve cross-border construction services, issues frequently arise regarding which law should govern the construction work contracts made by the parties. This is considering that Law Number 2 of 2017 on Construction Services in Indonesia stipulates that construction work contracts are subject to Indonesian law. However, in the provision of cross-border construction services, contractors will also perform some construction services in other jurisdictions and must comply with the regulations in those jurisdictions. This article, using an empirical juridical research method, will discuss the concepts of choice of law and choice of forum relevant to construction disputes. The construction disputes discussed here are not only those related to construction work contracts but also those related to building failures. From the study conducted, it is found that in determining the choice of law, the parties must also comply with mandatory legal principles applicable to the construction project. Furthermore, the choice of forum will be somewhat influenced by the choice of law agreed upon by the parties. However, for construction disputes not related to construction work contracts, the choice of law and forum becomes less relevant because the responsibility that arises is not based on a contractual relationship but on legal principles that protect the aggrieved party.